The natural history of spinal deformity in patients with Coffin-Lowry syndrome. (February 2018) - Welborn, M.; Farrell, S.; Knott, P.; Mayekar, E.; Mardjetko, S.
Purpose: Little is known about the natural history of spinal deformities in Coffin-Lowry syndrome (CLS). Our goal was to evaluate the spinal deformity progression and clinical impact. Methods: In this institutional review board-approved study, we performed a multinational retrospective review of six male CLS patients, aged 13 to 22 years at final follow-up, for a mean of 7.25 years (3 to 13). Results: All showed delayed skeletal maturity. Three had calcifications of their lower cervical ligamentum flavum, all experienced neural axis abnormalities, including lower extremity weakness, numbness and tingling and in one, quadriparesis. Only two were ambulatory at final follow-up. All had significant spinal abnormalities, including severe progressive thoracic lordosis, thoracolumbar kyphosis and scoliosis. All had undergone spinal fusion or were being evaluated for surgery. Conclusion: CLS is a rare X-linked mutation in the RSK2 gene, affecting between 1/50 000 to 100 000 people. There are two reports in the literature of patients with calcifications of their ligamentum flavum. Both had neural axis abnormalities and one had acute onset quadriplegia. Analysis of their ligamentum flavum found abundant central calcifications. Despite our small cohort we found 50% had calcifications and 100% had neurologic consequences associated with those calcifications. There was a 100% rate of deformity progression. They all exhibited delay in skeletal maturity, which mandates longer follow-up and has implications for surgical planning. From our cohort and literature review, the natural history of CLS supports frequent patient evaluation and a lower threshold for correction of spinal deformities. Aiming to avoid spinal cord compression and improve or avoid neurological deterioration. Level of Evidence: IV - retrospective study